MINISTER OF EDUCATION II WISHES SELAMAT HARI RAYA TO THE USM COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
The Minister of Education II Dato’ Seri Idris Jusoh wishes Selamat Hari Raya Aidil Fitri to the whole community of Universiti Sains Malaysia (USM). “As an alumni member of USM, I would like to wish Selamat Hari Raya Aidil Fitri to everyone and pray for a more wonderful Hari Raya this year than of previous years,” said Idris.